Outstanding Debt and the Household Portfolio - Becker, Thomas A.; Shabani, Reza (Review of Financial Studies, 2010)
This article examines the effect of household debt on investment decisions. We alter a simple portfolio choice model to allow households to retire outstanding debt and realize a risk-free rate of return equal to the interest rate on that debt. Using the Survey of Consumer Finances, we find that households with mortgage debt are 10 % less likely to own stocks and 37 % less likely to own bonds compared to similar households with no mortgage debt. We calculate the costs of nonoptimal investment in the presence of various forms of household debt. We find that 26 % of households should forgo equity market participation on account of the high interest rates they pay on their debt. (JEL D03, D12, D14, G11, G12) This article examines the effect of debt on the household portfolio. Whereas standard portfolio choice models focus primarily on the asset side of the house-hold balance sheet, we examine the effects of liabilities on investment deci-sions. Throughout the life cycle, many households accumulate debt from a variety of sources including mortgages, student loans, and consumer debt. Re-tirement of this debt offers households a return equal to the interest rate on their loan, which is almost always greater than the return to investing in the